(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
New finds of well-preserved remains of coiled nautiloids from lower Moscovian sediments (Kamenskaya Formation) of the Donets Basin (eastern Ukraine) allowed to describe the color pattern on the conch surface of species of the genera Parametacoceras, Metacoceras, Coelogasteroceras and Ephippioceras. The conch color pattern of the studied nautiloids is represented by longitudinal light bands along the ventrolateral shoulder (Parametacoceras and Metacoceras), transverse thin lines on the venter (Ephippioceras), and a black spot on the body chamber (Coelogasteroceras). Described color patterns represent disruptive coloration. Environmental conditions, e.g. slow sedimentation, absence of agents of mechanical and chemical destruction, dysaerobic conditions and rapid burial were obviously the most important factors for the preservation of coloration on the studied conchs of coiled nautiloids.